SURVIVAL STRATEGIES, REMITTANCE MANAGEMENT MODELS, AND MICRO BUSINESSES OF MIGRANT WORKER FAMILIES: A LITERATURE REVIEW - Habbi Firlana; Anida Sri Rahayu Mastur (Polteknik Imigrasi, 2023)
Indonesian Migrant Workers families employ various survival strategies, including saving, debt management, enhancing skills, and utilizing technology. These strategies help them cope with the challenges they face and improve their well-being. In terms of remittance management models, Indonesian Migrant Workers families utilize both formal and informal channels for sending and receiving remittance. They alson engage in micro business, such as culinary ventures, laundry services, and handicrafts, to generate additional income and meet their daily needs. However, Indonesian Migrant Workers families encounter challenges in establishing and sustaining micro business, such as limited capital, restricted market access, and lack of business management skills. To address these challenges, training programs, education, and broader market access are recommended to echance the success of micro businesses. The government plays a crucial role in supporting the well-being of Indonesia Migrant Workers families by implementing policies that facilitate the development of micro businesses and effective remittance management.